Interreligious Marriages: Can Couples in Interfaith Marriages Live a Happy Life? - Rasyid, Arbanur; Siregar, Fatahuddin Aziz (Universitas Islam Negeri Jakarta, 2025)
This article posits that families of interfaith couples (Muslims and Christianity/Catholicism) can achieve a state of happiness. Research data were obtained through in-depth interviews with married couples comprising one Indonesian and a British partner, aged between 25 and 40 years, residing in Indonesia and the United Kingdom, and representing diverse religious and cultural backgrounds The study revealed that the Islamic concept of sakīnah family embodies a totality of mercy (raḥmah) and love (mawaddah) inherently present in each couple's heart. The findings suggest that happiness in interreligious or interfaith marriages can be attributed to the profound love shared by the spouses. Love can develop and grow in a romantic, intimate, passionate, and committed relationship, provided there is a willingness to accept responsibility for maintaining it. Accordingly, these research findings may have implications for a new understanding of the sakīnah family, which, thus far, has been based upon the standard of couples having a common faith in a same-religion marriage. Nonetheless, further studies are needed to investigate whether couples in interfaith and interreligious marriages continue to lead happy lives in their old age. Abstrak Artikel ini menjelaskan bahwa keluarga pasangan beda agama (Muslim dan Kristen/Katolik) bisa mencapai kehidupan yang bahagia. Data penelitian diperoleh dari wawancara mendalam dengan pasangan dari latar belakang agama dan budaya yang berbeda berusia 25-40 tahun yang berasal dari Indonesia dan Inggris. Penelitian menemukan bahwa konsep keluarga sakinah dalam ajaran Islam adalah totalitas rahmat (raḥmah) atau cinta (mawaddah) yang ada dan melekat dalam hati setiap pasangan. Temuan penelitian menunjukkan bahwa kebahagiaan dalam hubungan suami istri dalam perkawinan beda agama dapat ditemukan karena besarnya rasa cinta yang dimiliki oleh pasangan tersebut. Cinta dapat tumbuh dan berkembang dalam suatu hubungan yang bersifat romantis, intim, penuh gairah dan komitmen serta kesediaan menerima tanggung jawab untuk menjaga hubungan. Dengan demikian, temuan penelitian ini memiliki implikasi pada pemahaman baru tentang keluarga sakinah, yang, sejauh ini, telah didasarkan pada standar pasangan yang memiliki keyakinan yang sama dalam pernikahan sesama agama. Meskipun demikian, studi lebih lanjut di masa depan diperlukan untuk mengamati apakah pasangan pernikahan beda agama dan antaragama masih menjalani kehidupan yang bahagia di usia tua mereka?